Tasyhir (exposure to the public) as an alternative punishment according to Islamic laws and its implementation in Malaysia - Husni, Ahmad Muhammad (Zes Rokman Resources (2131022-P), 2024)
Generally, takzir is infinite or is not bound by a particular type of punishment. It can be applied to anyone who makes mistakes regardless of their age and religion. One of the forms of takzir punishment is tashir, which is to expose the public to the offender's wrongdoing in a variety of ways, including calling it a call that hurts them. This article aims to explain the alternative forms of punishment according to Islamic Law and how it is implemented in Malaysia. Although its approach today is somewhat different from the previous one, however, the sentence is seen as elusive and still relevant to be used. One of their forms of execution is to publish the perpetrator's fault using mass media the aim is to achieve the same purpose of teaching the public so they will not be repeating the same mistake. This research uses qualitative methods by collecting the data and the views of the scholars on the tasyhir and the way it was practiced from the time of Rasulullah s.a.w up to present days. The analysis found that the way tasyhir punishment was implemented in ancient times to this day is still same where it uses the approach to advertise criminals for public viewing. However, nowadays, public broadcasts are partially carried out even without a court order. This requires special control so that no one is mistreated or publicly notified before they are found guilty